1962
DOI: 10.1107/s0365110x62003771
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of iron pentacarbonyl

Abstract: angle. It seems likely then that the 'double' bonds in the complex are intermediate in length to a normal single and a normal double bond.We feel that we have obtained all of the information on the ring geometry which is possible with the present visual intensity data. We agree with Baenziger et al. (1961) that in this type of problem better data are probably required if significant information on ring geometry is to be obtained. (1961). and [110] at temperatures ranging from --70 to --110 °C. The crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 3 publications
2
22
0
Order By: Relevance
“…The single scattering and multiple scattering paths are described in Figure . According to the fitting results, the averaged Fe–C bond length of 1.813(3) Å and C–O bond length of 1.144(7) Å were consistent with the values of 1.806–1.832 Å for Fe–C bond length and 1.127–1.153 Å for C–O bond length reported by single-crystal data , and electron diffraction experiments. Moreover, our EXAFS fitting result is consistent with Robertson’s that, which are 1.813(3) Å for the Fe–C length and 2.948(4) Å for the Fe–O length; the Fe–O lengths are slightly varying and their difference is about 2 standard deviations.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The single scattering and multiple scattering paths are described in Figure . According to the fitting results, the averaged Fe–C bond length of 1.813(3) Å and C–O bond length of 1.144(7) Å were consistent with the values of 1.806–1.832 Å for Fe–C bond length and 1.127–1.153 Å for C–O bond length reported by single-crystal data , and electron diffraction experiments. Moreover, our EXAFS fitting result is consistent with Robertson’s that, which are 1.813(3) Å for the Fe–C length and 2.948(4) Å for the Fe–O length; the Fe–O lengths are slightly varying and their difference is about 2 standard deviations.…”
Section: Resultssupporting
confidence: 89%
“…Carbon monoxide (CO) is one of the important ligands that can be a σ donor or a π acceptor in metal–carbonyl complexes so as to own some special characters in chemical bonding, like strong field ligand, semibridging ligand, and cis effect . It plays an important role in organometallic synthesis, catalysis, biological processes, and materials chemistry. For example, iron pentacarbonyl (Fe­(CO) 5 ) has various applications such as flame inhibition, soot suppressibility, and as a precursor for focused electron-beam-induced deposition (FEBID). In general, the trigonal bipyramid geometry ( D 3 h symmetry) is the most common structure for gas and solid phases of Fe­(CO) 5 , and the square pyramid geometry ( C 4 v symmetry) is a transition state of Berry pseudorotation. , However, the C 4 v and C 2 v structures may be stabilized by interactions with a solvent molecule located at the trans to rotational axis of a CO ligand. In general, infrared spectroscopy is often used to characterize metal–carbonyl complexes. Besides, X-ray absorption spectroscopy (XAS) is another technique to characterize the change of metal sites in such metal–carbonyl complexes due to the element-specific character of XAS.…”
Section: Introductionmentioning
confidence: 99%
“…The data (Hanson, 1962) used in both crystal structure refinements were collected from 3 zones each at a different temperature and they are not extensive for a monoclinic space group (317 observed reflexions). With data of higher quality the standard deviations obtained in these refinements could probably be improved.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of iron pentacarbonyl, Fe(CO)5, has been investigated by A.W. Hanson (1962), and further refined in an alternative space group by Donohue & Caron (1964). These studies showed that the molecular structure is, within experimental error, a trigonal bipyramid, with the carbon atoms of the car-bonyl groups bonded to the iron atom.…”
Section: Introductionmentioning
confidence: 99%
“…Iron with a coordination number of five has recently been shown (Hanson, 1962;Donohue & Caron, 1964) to have a trigonal bipyramid configuration in iron pentacarbonyl. However, this coordination number is still sufficiently unusual for the structure of monoo-phenylenebisdimethylarsine tricarbonyl iron(0), Fe(CO)3(As(CH3)2)zC6H4, to be of interest.…”
Section: Introductionmentioning
confidence: 99%